Mathematics achievement emotions: Global trend, emotional treatment, and directions for future research - Suparman, Suparman; Juandi, Dadang (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: The development of studies related to achievement emotions in mathematics learning has been increasingly grown in two last decades. Achievement emotions is one of significant predictors for students’ mathematics achievement. Nevertheless, to date no publications have been found that particularly review studies regarding mathematics achievement emotions.Aim: Present study highlights global trend of studies in mathematics achievement emotion for future research and examines the effect of emotional treatment on achievement emotions in mathematics across treatment type, treatment duration, and emotional type.Method: A systematic review using bibliometric analysis and meta-analysis was applied to do this study in which 223 documents from Scopus database published in the period of 2004 – 2023 were used as the data. To analyze the data, this study was promoted by some software, such as PoP, VOSviewer, and CMA.Result: Results revealed that global trends of studies regarding mathematics achievement emotions describe that number of publications slightly increased while number of citations relatively fluctuated from 2004 to 2023. There were several main themes which emerged in two last decades related to mathematics achievement emotions, such as emotional type, emotional treatment, activities-and outcomes-related emotion, mathematics content, and factors-related emotion. Moreover, emotional treatments slightly increased students’ positive emotions and decreased students’ negative emotions.Conclusion: This implies that the stability of mathematics achievement emotions of students in doing mathematics activities has to be generated to promote students’ mathematics achievement in which a few of emotional treatments, such as psychological therapies and web-based learning can be applied to stabilize students’ mathematics achievement emotions.